Epidemiologi Dan Diagnosis Dengue Di Indonesia - Zilhadia, Zilhadia (UI Scholars Hub, 2007)
Dengue fever/DF and dengue hemorrhagic fever/DHF is a global public health problem that occured in tropical and subtropical region. Epidemic dengue occurs every years, and it continues to be a major health problem in Indonesia. Due to its asymptomatic nature, a reliable, rapid and accurate dengue diagnosis is needed. Dengue diagnosis method based on molecular dengue virus properties and it will be developed by researcher. Dengue rapid test isnewly method. This article explaine about dengue epidemiology, molecular dengue virus properties, clinical diagnosis, serology diagnosis and progress research of dengue virus.